2010
DOI: 10.14569/ijacsa.2010.010104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of information systems on end user performance: A proposed model

Abstract: Abstract-In the last decades, information systems (IS) researchers have concentrated their efforts in developing and testing models that help with the investigation of IS and user performance in different environments. As a result, a number of models for studying end users' systems utilization and other related issues including system usefulness, system success and user aspects in business organizations have appeared. A synthesized model consolidating three well-known and widely used models in IS research is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…The users can favourable evaluate a not so good system due to various factors such as accessibility, ease of use, and personal characteristics [16,26]. Our conclusion regarding the TAM model is in accordance with that of other researchers [15,40,45,46], namely that the traditional TAM cannot fully explain adoption by users in the ERP context.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The users can favourable evaluate a not so good system due to various factors such as accessibility, ease of use, and personal characteristics [16,26]. Our conclusion regarding the TAM model is in accordance with that of other researchers [15,40,45,46], namely that the traditional TAM cannot fully explain adoption by users in the ERP context.…”
Section: Discussionsupporting
confidence: 85%
“…In a study from Esteves&Bohorquez (2007), the authors found that, from the total number of ERP publications that they have included in their research, 47% were concerning the implementation phase only, and a mere 15% the postimplementation phase. All three models have proven to be applicable in ERP, but each of them has certain limits due to the narrowness of focus or inadequately developed methodologies [40]. That is why it often happens that, in many studies which aim at being exhaustive, these models are combined together, or used in combination with other models and theories which are not covered by this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sistem informasi dianggap memiliki dampak yang siqnifikan pada pekerjaan pengguna sistem, beberapa penelitian menegaskan bahwa sistem informasi dapat meningkatkan produktivitas dan meningkatkan hasil dan kinerja (Abugabah, et al (2009). Menurut Goodhue dan Thomson (1995) menyatakan bahwa pencapaian kinerja individu berkaitan dengan pencapaian atas rangkaian tugas-tugas dengan dukungan sistem informasi yang ada.…”
unclassified